Pengaruh Umur Perusahaan, Ukuran Perusahaan, Return On Asset Dan Debt to Equity Ratio Terhadap Underpricing Saham Pada Perusahaan Jasa Saat Initial Public Offering (IPO) Di Bursa Efek Indonesia (BEI) Periode 2020-2023 - M. Fatkhur Rohman; Ika Rosyada Fitriati (CV. Ulil Albab Corp, 2024)
A This study aims to determine whether there is an effect of Company Age, Company Size, Return On Asset, and Debt Equity Ratio on the Level of Underpricing of shares in Service Companies during IPO on the Indonesia Stock Exchange. The independent variables used are Company Age, Company Size, Return On Asset, and Debt Equity Ratio. The dependent variable used is Underpricing. The population in the study were Service Companies listed on the Indonesia Stock Exchange (IDX) in the 2020-2023 period. This research method uses an associative approach. Sampling using purposive sampling technique, namely sample selection with certain criteria, so that the sample in this study was obtained as many as 57 companies .